TINGKAT ASOSIASI JENIS-JENIS BENALU DENGAN POHON INANGNYA DI BLOK KOLEKSI TAMAN HUTAN RAYA WAN ABDUL RACHMA - Debi Pratiwi Putri; Indriyanto Indriyanto; Melya Riniarti (Jurnal Hutan Tropis, 2021)
Arboreal plant species is one of a group of parasitics plants that belong to the Loranthaceae family.  Trees or shrubs that are attacked by parasitics would be disturbed and might even die if the attack is in wide numbers.  Wan Abdul Rachman Great Forest Park is an area to maintain the nutrient cycle and biodiversity preservation center for Lampung Province.  Wan Abdul Rachman Great Forest Park is divided into five wide blocks, one of which is the collection block, with an area of 2,120.10 ha or around 9.53% of the total area.  The objective of this study i.e to determine the species of parasitcs at Collection Block of Wan Abdul Rachman Great Forest Park, determine the species of host plants associated with the species of parasitcs, and analyze the density of each parasitics population.  This research was conducted on JuneJuly 2019 using a systematically arranged plot methods.  Sample plots have 70 the form rectangle measuring 20m x 20m.  The results of this study were found 4 species of parasitics, which were 7 species of host plants.  The parasitics population which has the highest density is Macrosolen cochinchinensis with a density value of 4.64 individuals / ha. The parasitics significantly associated with the ketupa tree obtained an (OI value 16.50) and significantly associated with the jackfruit tree (OI value11.60).  while the parasitics population that had the smallest density was Scurrula philippensis with a density valueof 0.71 individuals / ha. The parasite is not significantly associated with the Tangkil tree (OI value 1.51)